Authentication Mechanism for Ad Hoc Wireless Local Area Network - M.A.C., Bhakti; Azween, Abdullah (2008)
Wireless networks have grown rapidly over the last decade and they have been deployed in numerous applications due to their advantages over wired networks, specifically for its mobility and convenience. However, due to its wireless nature, some security issues in wireless network need to be addressed, such as unauthorized or rogue wireless devices which are relatively easy to connect to the network because they do not need any physical access. These issues might prevent further acceptance and adoption of wireless network technology. One of the solutions to overcome the wireless network security is the 802.1X specification. It is a mechanism for port-based network access control, which based on Extensible Authentication Protocol (EAP). It is an authentication framework that can support multiple authentication methods. This research is looking into the possibility of using EAP as a generic authentication mechanism in ad hoc wireless local area networks. One promising advantage of using EAP-based authentication mechanism in a network is its interoperability with other types of networks since EAP is already a platform for various authentication mechanisms. This thesis studies and explores the feasibility of using EAP in ad hoc wireless local area network and then proposes a mechanism to implement EAP in ad hoc wireless local area network based on EAP multiplexing model. This thesis also proposes an extension to EAP, a mechanism to select a suitable EAP method out of a set of EAP methods to be used in EAP authentication process in heterogeneous mobile devices environment, where the network consists of different types of nodes / devices with different specifications and capabilities, and each node may support different type of EAP authentication method. Toward the end of this thesis, formal specification and verification of the proposed authentication mechanism are derived and strong final beliefs are obtained. Furthermore, node architecture that can be used in simulation of EAP authentication is designed and the EAP method selection mechanism is simulated.